INSPEKSI CACAT (DISKONTINUITAS) PADA MATERIAL DENGAN MENGGUNAKAN UJI ULTRASONIK DAN UJI RADIOGRAFI - Pitalokha, Renie Adinda; Mulyana, Cukup; Hamdani, Muhamad Ridwan; Muhammad, Fajar (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Defect (discontinuity) in the material can be caused by the damage of microscopic or macroscopic structure of material and can’t be visually inspected. Non-destructive testing is one of material testing without destruct the material, so it can act as quality control which defect of material can be detected. One of the method used in radiography testing uses x-ray as defect detector and showing the result in negative film or computer. Whereas the principle of ultrasonic testing uses audible wave with high frequencies to find out the characteristics of defect. Ultrasonic testing have been developed into phased array ultrasonic testing and long range ultrasonic testing. This research will compare both of ultrasonic testing and radiography testing from the principle, proccess, capabilities, and limitations. Long range ultrasonic testing have capablity to determine the location of defect. Phased array ultrasonic test have capablity to detect the type of defect from small defect to small material, while x-ray radiograph testing can indentify type and shape of the defect. These methods were not showing which one the best is, but they were complete each other. Keywords: ultrasonic testing, radiography testing, x-ray, non-destructive testing.